From Specific Training to Global Shift of Manual Preference in Kung Fu Experts. Issue 1 (February 2014) - Maeda, Rodrigo S.; Souza, Rosana M.; Teixeira, Luis A.
Manual preference and intermanual performance asymmetry have been approached from a multidimensional and dynamic perspective. A point of interest from that approach is the role of lateralized motor experiences on handedness. In this study, intermanual performance asymmetry in sport-specific movements and manual preference in daily living tasks were compared between Kung Fu athletes and novices. Analysis of movement time in the performance of interlaterally symmetric and asymmetric movement patterns showed smaller intermanual performance asymmetry in experts. Analysis of manual preference using the Edinburgh Handedness Inventory indicated that experts presented predominantly weak or moderate strength of right hand preference. Novices, conversely, were found to have predominantly strong right hand preference. These results suggest that extensive bimanual training by experts leads to a global shift of manual preference, affecting hand selection in distinct tasks.